Dysregulated mitochondrial and cytosolic tRNA m1A methylation in Alzheimer's disease. Issue 10 (13th December 2021) - Shafik, Andrew M; Zhou, Huiqing; Lim, Junghwa; Dickinson, Bryan; Jin, Peng
Abstract: RNA modifications affect many aspects of RNA metabolism and are involved in the regulation of many different biological processes. Mono-methylation of adenosine in the N1 position, N1-methyladensoine (m 1 A), is a reversible modification that is known to target rRNAs and tRNAs. m 1 A has been shown to increase tRNA structural stability and induce correct tRNA folding. Recent studies have begun to associate the dysregulation of epitranscriptomic control with age-related disorders such as Alzheimer's disease. Here, we applied the newly developed m 1 A-quant-seq approach to map the brain abundant m 1 A RNA modification in the cortex of an Alzheimer's disease mouse model, 5XFAD. We observed hypomethylation in both mitochondrial and cytosolic tRNAs in 5XFAD mice compared with wild type. Furthermore, the main enzymes responsible for the addition of m 1 A in mitochondrial (TRMT10C, HSD17B10) and cytosolic tRNAs (TRMT61A) displayed decreased expression in 5XFAD compared with wild-type mice. Knockdown of these enzymes results in a more severe phenotype in a Drosophila tau model, and differential m 1 A methylation is correlated with differences in mature mitochondrial tRNA expression. Collectively, this work suggests that hypo m 1 A modification in tRNAs may play a role in Alzheimer's disease pathogenesis.